Beef Cattle on Pasture Have Better Performance When Supplied With Water Trough Than Pond - Bica, Gabriela Schenato; Pinheiro Machado Filho, Luiz Carlos; Teixeira, Dayane Lemos (Frontiers in Veterinary Science, 2021)
The behavior and performance of steers on pasture regarding water availability in troughs or in ponds were compared. Eight paddocks were randomly allocated to one treatment: POND (~30 m of diameter) or TROUGH (water trough, 120 cm diameter and 60 cm high and 500 L capacity). Eight groups of six beef steers were randomly assigned to one of the paddocks. The first 10 days were considered for animal habituation. Animals were individually weighed (days 0, 30, 60, and 90). Beginning in the day after each weighing on days 30 (Month 1), 60 (Month 2), and 90 (Month 3), behavior and animal distribution in the paddock were recorded by direct visual observation in three periods of 4 consecutive days. Water temperature and fecal and herbage DM were also recorded in these periods. Water intake was measured during 16 random days in the troughs. Data were analyzed using Generalized Linear Mixed Models, with treatment and period as fixed effects. TROUGH steers gained more weight (0.44 vs. 0.34 kg/day/animal; P ≤ 0.007) during the experiment and were heavier than the others at the end of the study (P ≤ 0.05). POND steers spent more time drinking water, but TROUGH steers increased the number of drinking events throughout the study (P ≤ 0.05), suggesting an adaptation for the new type of water source. Both treatments increased grazing time throughout the study, but not ruminating time (P ≤ 0.05). Walking time differed between treatments in all periods of behavior observation (P ≤ 0.05). Events of animal licking and ingesting salt of POND steers reduced throughout the study (P ≤ 0.05). The number of drinking events of TROUGH steers increased throughout the study, and drinking events were longer for POND steers than TROUGH steers (P ≤ 0.05). TROUGH steers spent more time on pasture on Month 2 (P ≤ 0.05). Period collection did not affect the water intake of TROUGH treatment (P > 0.05). This study demonstrates that water available in troughs rather than ponds for steers on pasture has positive effects on their weight gain and affects cattle behavior.